Analysis of The Need for The Development of Local-Based English Teaching Materials to Improve Reading Literacy in High School Students - Makhroji Makhroji; Irma Dewi Isda (STAI Hubbulwathan Duri, 2023)
The teaching materials used are English teaching materials which contain local learning concepts that increase the discussion of how to read English correctly in pronouncing words in accordance with grammar. Therefore, English teaching materials are very useful for students to master reading literacy skills. English is also part of the international language contained in the subjects applied in schools. In this case, students are required to have English teaching materials as a guide in mastering English knowledge and are also able to compete nationally and internationally. Thus, the purpose of this study was born, namely to determine the analysis of the need for the development of locally based English teaching materials to improve reading literacy. This research uses a design research development method that takes the form of a type of study validation. The basis of the use of this type of method proves from the theory of learning at the stage of needs analysis. The results of the study show that the usefulness of local learning teaching materials can increase students' reading literacy more independently. Local learning teaching materials can make it easier for teachers to be used as a source of learning media. The conclusion of this study is that local learning teaching materials can be implemented for learning activities and English language learning is more practical and easy to understand .